A MECHANISM TO EXPLAIN SUDDEN CHANGES IN RATES AND PRODUCTS FOR PYRRHOTITE DISSOLUTION IN ACID SOLUTION - Thomas J.E.; Skinner W.M.; Smart R.S.C. (My University, 2001)
A reductive mechanism is proposed to explain the sudden changes from oxidative (acid-producing) to nonoxidative (acid-consuming) dissolution that can occur with pyrrhotite. Typically, in acidic conditions, an initial period of slow dissolution involving no release of H2S can suddenly change to nonoxidative dissolution, with release of H2S and greatly increased rates of release of both iron and sulfur species. Observations of the change from oxidative to nonoxidative dissolution of pyrrhotite in deoxygenated acid show that the process is temperature sensitive, with solution temperatures of at least 40°C required.The mechanism is correlated with the observation from XPS analysis that pyrrhotite surfaces exhibit metastable chemical states that have trapped electrons. The same negative charge shift is measured for all C, Fe, and S chemical states implying a crystal-wide space-charge surface region. The accumulation of this surface charge during dissolution appears to result in the reduction of oxidised disulfide and polysulfide species back to sulfide, thus inducing nonoxidative dissolution. Reduction is favoured on natural pyrrhotite surfaces polished in an oxygen-free atmosphere. Reduction also occurs with synthetic pyrrhotite that, before dissolution in acid, has undergone only limited oxidation. The mechanism is minimal or nonexistent if, before dissolution in acid, the pyrrhotite (natural or synthetic) is ground either in air or in a N2 atmosphere. No evidence for this mechanism is found with either polished or ground pyrite dissolving in acid under the same conditions. Reduction of pyrite only occurs with the application of a sufficiently cathodic potential.